Analytical andnumerical study of the bifurcation of a cylindrical bar under uniaxial tension - Durand, Sabine; Combescure, Alain (European Journal of Computational Mechanics, 1999)
The influence of plasticity theory on the bifurcation of a cylindrical bar under large tensile strain is analyzed. A deformation theory of plasticity is assumed and the eigenvalue problem governing bifurcation is solved. A comparison is made between this solution and one obtained with a flow theory. The problem is then solved by means of the finite element method. Numerical computations are conducted for different geometries and material parameters and the results are compared with the analytical predictions.